PERILAKU GETARAN PAKSA TEREDAM PADA TABUNG TERBENAM MENGAMBANG (SUBMERGED FLOATING TUBE) YANG MENDAPAT GAYA GANGGUAN GELOMBANG - Jamiatul Akmal; Novri Tanti; Martinus Martinus; Thomas Wisudarma; Muhammad Yakuti Arsi (Jurnal Sains dan Teknologi, 2021)
In the maritime structure, there are many cylindrical structures found at various depths of the sea (submerged floating tube / SFT). Some examples of application are submarine pipe structures, structural support poles, and recently, tunnel structures have been developed for inter-island transportation. This article presents the dynamic behavior of SFT which covers the wave action force, hydrodynamic damping factor and amplitude response to damped vibrations. The wave action force refers to the Morison equation, the damping factor is based on the dragforce which is influenced by flow velocity and geometric factors. Measurement data were analyzed non-dimensionally. The conclusion is that the resulting formula can be used to predict the wave action force on a floating immersed tube at several depth positions, the damping factor and the amplitude of the damped vibration.